Equity is efficient! - Hanžek, Matjaž (Družboslovne razprave, 1999)
There is a number of economic theories claiming that economic growth is accelerated by increasing inequality. Inequality is said to force people to work harder and more efficiently. On the other hand, other economists disagree with this theory claiming that increased inequality hinders economic growth, especially indirectly through greater social problems. Although the sociological science does not have a firm position concerning this matter it underlines the negative social components of inequality. The author of this paper tries to prove - using the example not only of transition but also of developed economies - that too wide inequality in distribution decreases economic growth, and at the same time increases social problems in a society.
Keywords: družbene razmere; gospodarski položaj; družbeni razvoj; družbena struktura; družbena diferenciacija; družbena neenakost